Development and characterisation of solvent-borne thermally cured cross-linked TiO2 reinforced Polyceramic coatings for long service-life on industrial metal substrates - Tan, O.; Cimen, O.; Yolcu, P.; Cicek, B. (ASSOC ITALIANA METALLURGIA, 2020)
Polyceramic coatings exhibit the properties of both polymer and ceramic coatings together, such as flexibility and pencil hardness. These coatings are intended to reduce the loss of capital, labour, and energy to achieve industry-required performance under different operating conditions, with long corrosion resistant service life. In this study, two-component polyceramic coatings with a TiO2 reinforced formula were produced and applied to two different metal surfaces, Sandblasted Aluminium 1050 plate and SAE 304 Stainless Steel sheet, in order to examine the mechanical, physical and chemical properties of the coatings. In addition, the polyceramic coatings were able to form a film on polypropylene plate and SA-66 Glass plate under curing conditions adjusted according to the substrate material, due to their very low surface energy. Resin-compatible solvents, TiO2 filler, carbon black pigment, resins and a crosslinker added according to the NCO/OH ratio were used in the production of the coatings. Experiments for coating metal substrates were carried out at curing temperatures between 120 and 180 degrees C, and at curing times between 60 and 120 minutes. In this study, coating formulations were investigated by SEM, EDS, FTIR, and TGA analysis. The coatings showed 8H pencil hardness, 5B level high adhesion to the metal surfaces, high flexibility with 180 degrees mandrel bending, hydrophobicity, and high corrosion resistance in a salt fog test carried out with 5% salt solution at 35 degrees C in for 700 hours, according to ASTM D3363, ASTM D3359, ASTM D522 and ASTM B117 standards.
Keywords: POLYCERAMIC COATINGS; HIGH CORROSION RESISTANCE; TWO-COMPONENT COATINGS; HIGH ABRASION RESISTANCE; METAL; CONTACT-ANGLE; ADHESION; Metallurgy & Metallurgical Engineering